„Powstanie sobie, życie sobie…” Obraz wydarzeń z lat 1919–1921 w prozie Szczepana Twardocha (PDF 459 KB) (Książnica Śląska, 2025)
The author discusses the presentation of the Silesian Uprisings in Szczepan Twardoch‘s prose. He mentions several heroes of the writer‘snovels to analyze their attitude towards events of the years 1919–1921. Referring to those events, they seem, depending on their personal motives, either detached or deeply emotional. Therefore, theuprisings themselves become for some more a personal vengeancethan a national spurt. It is clear, that for Twardoch the process of aprotagonist‘s identity formation is far more significant than the subject of the uprisings.